STRATEGI VENTILASI ALAMI UNTUK MENINGKATKAN KENYAMANAN DI RUMAH TRADISIONAL SUKU BAJO : STUDI KASUS PADA DESA LEMO BAJO KECAMATAN LEMBO KABUPATEN KONAWE UTARA - Roulus, Mamang (FAKULTAS TEKNIK UMKENDARI, 2024)
This research examines natural ventilation strategies in traditional houses of the Bajo tribe in Lemo Bajo Village, Lembo District, North Konawe Regency. The study aims to identify and analyze natural ventilation patterns applied to traditional Bajo tribal houses and their impact on occupants’ thermal comfort. The research method uses qualitative and quantitative approaches with direct measurements of temperature, humidity, and wind speed at several points inside and outside the building. The results show that the natural ventilation design of Bajo tribal houses has unique characteristics formed from adaptation to the coastal climate. Proper opening applications, building orientation according to wind direction, and local materials contribute to creating a comfortable thermal environment. This research provides recommendations for developing more optimal natural ventilation designs in traditional Bajo tribal houses.